The Impact of Parental Divorce on Children's Psychology - Maryam Luailik; Elok Halimatus Sa’diyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The impact of divorce has a big influence on the psychological aspects of children, and the effects can continue into adulthood. Young adults' ability to form relationships that fulfill their developmental tasks is influenced by how they interpret and attribute parental experiences of romantic relationships. Research using the narrative review method aims to better understand the psychological impact on young adults who experience their parents' divorce. The research results show that divorce can have both positive and negative impacts on children's psychological conditions, which in turn affects their ability to form relationships appropriate to the developmental stages of young adults, especially those related to intimacy vs isolation. Therefore, it is important to explore these dynamics and identify the factors that influence success in forming relationships so that individuals who have the experience of parental divorce can cope with their developmental tasks optimally. With a deeper understanding, we can provide more effective support to young adults experiencing parental divorce to overcome its psychological impact and form healthy romantic relationships.